2020
DOI: 10.3389/fnhum.2020.568395
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Water Imaging Demonstrates Lower Brain Myelination in Children and Adolescents With Poor Reading Ability

Abstract: Magnetic resonance imaging (MRI) provides a means to non-invasively investigate the neurological links with dyslexia, a learning disability that affects one's ability to read. Most previous brain MRI studies of dyslexia and reading skill have used structural or diffusion imaging to reveal regional brain abnormalities. However, volumetric and diffusion MRI lack specificity in their interpretation at the microstructural level. Myelin is a critical neural component for brain function and plasticity, and as such, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 116 publications
(144 reference statements)
0
16
0
Order By: Relevance
“…To date, only one study has directly investigated the relationship between MWF and reading ability. In a sample of 20 participants aged 10-18 years old, Beaulieu et al (2020) reported positive correlations between reading and MWF, as well as lower MWF in poor (n=7) compared to good readers (n=11) in several regions including bilateral thalamus, centrum semiovale, anterior and posterior limbs of the internal capsule and splenium of the corpus callosum. This study offers new insights into the relationship between myelin water and reading, however replication of these ndings is warranted given the small sample size, the wide age range and the selection of regions which are not typically considered part of the core reading circuitry.…”
Section: Introductionmentioning
confidence: 92%
“…To date, only one study has directly investigated the relationship between MWF and reading ability. In a sample of 20 participants aged 10-18 years old, Beaulieu et al (2020) reported positive correlations between reading and MWF, as well as lower MWF in poor (n=7) compared to good readers (n=11) in several regions including bilateral thalamus, centrum semiovale, anterior and posterior limbs of the internal capsule and splenium of the corpus callosum. This study offers new insights into the relationship between myelin water and reading, however replication of these ndings is warranted given the small sample size, the wide age range and the selection of regions which are not typically considered part of the core reading circuitry.…”
Section: Introductionmentioning
confidence: 92%
“…Disrupted, altered or less effective connections between brain regions supporting academic learning are related to learning disabilities, such as dyslexia, which is linked to inefficient communication between brain regions. Significantly lower MWF values have been found in children categorized as 'poor readers', further supported by a significant positive correlation between MWF and age-standardized reading scores [15]. Recent work also found that students who showed greater improvement in working memory after cognitive intervention had higher baseline MWF [16].…”
Section: Early Developmentmentioning
confidence: 92%
“…This larger sample exhibited 10% missingness across predictor variables in the multiple imputation model, which included age, sex, research site, as well as standardized scores for phonological decoding (Word Attack [ 118 , 119 ]), real word identification (Letter–Word Identification [ 118 , 119 ]), reading comprehension (Passage Comprehension cloze task [ 118 , 119 ]), rapid naming [ 120 , 121 ], and verbal comprehension [ 122 , 123 ]. These measures were requested during multisite data collection, in part because they have been used in previous studies to demonstrate brain structure and behavior associations, particularly for the Word Attack phonological decoding measure [ 9 , 39 , 41 , 72 , 124 , 125 ]. There was 6% and 14% missingness in the pediatric and adult samples, with a low percentage of phonological decoding missingness (0.4%, 8%), respectively.…”
Section: Methodsmentioning
confidence: 99%